Was Lysias 1 Delivered in an Athenian Court? - Wolpert, Andrew (Scripta Classica Israelica, 2025)
The defendant of Lysias 1 relies unnecessarily on fallacious legal arguments. The law on justifiable homicide permitted the kurios to kill a man whom he caught 'in the act' with a legitimate Athenian woman under his guardianship. However, it did not require the guardian to do so, and it did not prevent the guardian from seeking an alternative punishment. Although the law on justifiable homicide does not address the intent or motives of the guardian or specify how the illicit act must be discovered for the killing to be legal, these are central issues in Lysias 1. Ironically, it would have been easier for Euphiletus to catch Eratosthenes in the act, and his case would have been just as compelling, if he had rushed into the bedroom as soon as he had learned that Eratosthenes was in his house rather than wait to kill the adulterer until after he had gathered witnesses and stopped at a nearby tavern for torches. Perhaps the logographer circulated the speech not to memorialize what he wrote for an actual client, but to entertain a reading audience. Thus, we cannot rule out the possibility that the speech is fictional.